1998
DOI: 10.1115/1.2830212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flyash Addition on the Quality of Al-11%Si Alloy Castings Produced by V-Process

Abstract: Energy is important for modern civilization and the electrical power from thermal stations is a major source of energy on which hinges the functioning and growth of mankind. In almost all major countries of the world thermal power stations are getting bigger and are generating huge quantities of flyash as a waste from their mammoth boilers. Despite extensive research on flyash, its utilization level is still low although it is considered as a novel and useful material in various fields such as building and roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…On the basis of this model, Singh and Singh (2011) studied the relationships between SH and controllable process parameters [14]. These relationships agree well with the trends observed by experimental observations made otherwise [8][9][10][11][12][13].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…On the basis of this model, Singh and Singh (2011) studied the relationships between SH and controllable process parameters [14]. These relationships agree well with the trends observed by experimental observations made otherwise [8][9][10][11][12][13].…”
Section: Introductionsupporting
confidence: 60%
“…The process uses a specially designed, strong, highly flexible polymer film to seal the open ends of the sand mould and form the mould cavity [8]. The literature review reveals that lot of work has been reported on optimization of VM process [9][10][11][12][13]. Various process parameters like: vibration frequency, pouring temperature and plastic film thickness for the sound casting produced by VM process have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated mean of the response characteristic surface roughness can be determined (Kumar, 1993 andRoy, 1990) The 95% confidence interval of the population is:…”
Section: Surface Roughnessmentioning
confidence: 99%
“…The literature review reveals that some research work has been reported on AMC development using vacuum moulding and stir casting process [17][18][19][20]22,[25][26][27]. But hitherto no work has been reported on the wear properties of AMC prepared with different particle size of solutes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moulding equipment is simple too [19][20][21]. In this process sand thermal conductivity is lower and metal fluidity is improved [22]. Stir casting involves introduction of reinforcement/abrasive particles into metal melt by stirring powders [23][24][25].…”
Section: Introductionmentioning
confidence: 99%